2012
DOI: 10.1159/000335155
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Brain Biopsy in Long-Term Prognostication of 468 Patients with Possible Normal Pressure Hydrocephalus

Abstract: Normal pressure hydrocephalus (NPH) can be alleviated by cerebrospinal fluid shunting but the differential diagnosis and patient selection are challenging. Intraventricular intracranial pressure monitoring as part of the diagnostic workup as well as shunting enable to obtain cortical brain biopsies to detect amyloid-β (Aβ) and hyperphosphorylated tau (HPτ), the hallmark lesions of Alzheimer’s disease (AD). In possible NPH, Aβ alone indicates an increased risk of AD and when present with HPτ probable AD, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 48 publications
6
33
1
Order By: Relevance
“…To date, we and others have not been able to detect soluble Aβ aggregates in human cerebrospinal fluid4049, though some groups have done so505152. Assessments of brain biopsy tissue from patients undergoing normal pressure hydrocephalus surgery, nearly half of whom may also have Aβ pathology53, represent a logical direction for addressing potential post-mortem artifacts. Direct detection in the brain using molecularly specific electrode technology may represent a novel approach54.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we and others have not been able to detect soluble Aβ aggregates in human cerebrospinal fluid4049, though some groups have done so505152. Assessments of brain biopsy tissue from patients undergoing normal pressure hydrocephalus surgery, nearly half of whom may also have Aβ pathology53, represent a logical direction for addressing potential post-mortem artifacts. Direct detection in the brain using molecularly specific electrode technology may represent a novel approach54.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence that iNPH may have a genetic component [2731]. We have previously observed that over 40% of iNPH patients present, on their cortical biopsies, with either beta-amyloid, hyperphosphorylated tau protein or both [8]. It has been reported that beta-amyloid and hyperphosphorylated tau protein accumulation in the brain is increased in Kaolin-aged hydrocephalic rats and it has been hypothesized that the accumulation is due to decreased CSF clearance [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid beta plaques and hyperphosphorylated tau-protein inclusions have been frequently identified in neuropathological studies and studies using frontal cortical biopsies in iNPH [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Multiple overlapping signs and symptoms between different types of cognitive impairment such as NPH, Alzheimer's disease and vascular dementia [2-4] create diagnostic challenges in patients with cognitive impairment. This motivates the development and investigation of novel noninvasive imaging techniques to serve as diagnostic tools for identifying patients with NPH.…”
Section: Introductionmentioning
confidence: 99%